Influence Social Media Marketing and Electronic Word-of-Mouth to Purchase Intention on Products Erigo Official Shop on Shopee Mediated by Brand Trust to Students Active in Malang City - Sirojuddin, Nur Muhammad; Sudarmiatin; Dhewi, Titis Shinta (Asian Journal of Management Analytics, 2024)
The digital era has revolutionized marketing dynamics and consumer behavior, offering marketers immense opportunities to leverage social media platforms and electronic word-of-mouth (E-WOM) for enhancing marketing strategies. This research investigates the impact of social media marketing and E-WOM on purchase intention, emphasizing the mediating role of brand trust. Targeting active student consumers in Malang City, particularly those transacting at the Erigo Official Shop on Shopee, the study employs a quantitative approach with 385 respondents. Through descriptive analysis and Structural Equation Modeling (SEM-PLS), the research reveals the positive influence of social media marketing and E-WOM on brand trust, subsequently affecting purchase intention. Additionally, mediation testing underscores the indirect effects of social media marketing and E-WOM on purchase intention mediated through brand trust. These findings shed light on the intricate mechanisms shaping consumer decision-making processes in the digital landscape, offering valuable insights for marketers navigating this dynamic terrain.